3RCity 2 (2017)
"3RCity is a serious game whose main goal is to illustrate part of the garbage recycling and treatment process. The original game was developed the first semester of the year 2017 as a component of the graduation project of the System and Computing Engineering students, Alejandro Zucchet Cárdenas and Omar Pino Reyes. That project consisted on the initial design and development of the game the corresponding documentation of the engineering process. The current project, 3RCity 2, is a continuation of said work. After developing a playable version, the game was exposed and user tested at the 2017 SOFA convention in Bogotá. The analysis of the feedback received was used to implement changes aimed to make the mechanics more understandable and improve playability. A final version was uploaded online and Unity Analytics functionalities were used to get gameplay data from the online players."--Tomado del Formato de Documento de Grado